2008
DOI: 10.1128/aem.00217-08
|View full text |Cite
|
Sign up to set email alerts
|

Purification and Characterization of a Novel Recombinant Highly Enantioselective Short-Chain NAD(H)-Dependent Alcohol Dehydrogenase from Thermus thermophilus

Abstract: The gene encoding a novel alcohol dehydrogenase (ADH) that belongs to the short-chain dehydrogenase/ reductase (SDR) superfamily was identified in the extremely thermophilic, halotolerant gram-negative eubacterium Thermus thermophilus HB27. The T. thermophilus ADH gene (adh Tt ) was heterologously overexpressed in Escherichia coli, and the protein (ADH Tt ) was purified to homogeneity and characterized. ADH Tt is a tetrameric enzyme consisting of identical 26,961-Da subunits composed of 256 amino acids. The en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
57
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 60 publications
(60 citation statements)
references
References 29 publications
3
57
0
Order By: Relevance
“…ChKRED20, predicted ketone reductase in this work, KC342020; LSADH, alcohol dehydrogenase from Leifsonia sp. S749, BAD99642 [31]; LK-ADH, R-specific alcohol dehydrogenase from Lactobacillus kefir, AAP94029 [28]; LB-RADH, R-specific alcohol dehydrogenase from Lactobacillus brevis, AJ544275 [32]; TtADH, alcohol dehydrogenase from Thermus thermophilus, 2D1Y [36]; CPADH, (S)-1-phenyl-1,2-ethanediol dehydrogenase from Candida parapsilosis, DQ675534 [29]. Gray shading indicates residues highly conserved in the SDR family.…”
Section: Discussionmentioning
confidence: 99%
“…ChKRED20, predicted ketone reductase in this work, KC342020; LSADH, alcohol dehydrogenase from Leifsonia sp. S749, BAD99642 [31]; LK-ADH, R-specific alcohol dehydrogenase from Lactobacillus kefir, AAP94029 [28]; LB-RADH, R-specific alcohol dehydrogenase from Lactobacillus brevis, AJ544275 [32]; TtADH, alcohol dehydrogenase from Thermus thermophilus, 2D1Y [36]; CPADH, (S)-1-phenyl-1,2-ethanediol dehydrogenase from Candida parapsilosis, DQ675534 [29]. Gray shading indicates residues highly conserved in the SDR family.…”
Section: Discussionmentioning
confidence: 99%
“…30 mg protein per litre of culture, and that this enzyme shows potential for applications involving bioconversions of substituted acetophenones and aromatic α-keto esters such as 1. [14] Kinetic studies showed that this latter compound was a better substrate when halogenated at the ortho position of the benzene ring. The k cat , K m and k cat /K m values determined for the reduction of 1 were 38.1 Ϯ 3.7 s -1 , 2.7 Ϯ 0.6 mm, and 14.1 s -1 mm -1 , respectively and those for 2 were 7.1 Ϯ 0.2 s -1 , 0.32 Ϯ 0.1 mm, and 22.2 s -1 mm -1 , respectively.…”
Section: Process Development Using Glucose Dehydrogenase For Cofactormentioning
confidence: 99%
“…[13] More recently, an NADH-dependent, highly enantioselective ADH (TtADH), identified from the thermophilic, halotolerant gram-negative eubacterium Thermus thermophilus HB27, has been purified and characterized in our laboratory. [14] The thermophilic enzyme catalyses the reduction of α-methyl and α-ethyl benzoylformate to methyl (R)-mandelate (ee = 91 %) and ethyl (R)-mandelate (ee = 95 %), respectively, by way of an in situ NADH-recycling system involving 2-propanol and Bacillus stearothermophilus ADH (BsADH). [14] This paper reports the enzymatic synthesis of 1a and 2a by TtADH and the evaluation of glucose dehydrogenase as well as BsADH for achieving cofactor regeneration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Particularly, employment of enzymes derived from thermophiles and hyperthermophiles enables the simple preparation of catalytic modules with excellent selectivity and thermal stability [5,12]. Furthermore, although the detailed mechanisms remain to be clarified, many thermophilic enzymes have also been reported to display higher tolerance towards denaturants such as detergents and organic solvents than their mesophilic counterparts [13,14], and activities of some thermophilic enzymes are even improved with organic solvents [15]. These excellent stabilities of thermophilic enzymes allow great flexibility in the operational conditions of in vitro bioconversion systems.…”
Section: Introductionmentioning
confidence: 99%